How does perceived partner’s affection and negativity contribute to one’s satisfaction with marriage? - Jelić, Margareta (Array, 2012)
Social learning theories assume that exchanging rewarding or positive behaviors during interactions between partners contributes to the quality of marriage, and exchanging punishing or negative behaviors does harm. The first goal of this study was to determine the relation between partners’ affection/negativity and their intensity of love and marital satisfaction. The second goal was to explore whether these patterns of interaction vary with gender, age, length of marriage and family structure. We gathered data from 302 married couples from Croatia of different ages (20-82 years) and various urban/rural backgrounds. Length of marriage varied between one month and 57 years. The Inventory of Affection and Negativity in Relationships (Huston, Kamenov and Huić, 2010), Love Scale (Braiker and Kelley, 1979) as well as a global measure of marital satisfaction were administered. Results confirmed the importance of partner’s behavior patterns during couples’ interactions on participants’ satisfaction with marriage. The perception of partner’s display of affection and negativity accounted for almost 50% of variance of relationship satisfaction, while the intensity of love toward partner explained an additional 20%. Participants were more satisfied with their marriage if their partners showed more affection and less negativity during their interactions. However, we found a significant interaction effect of affection and negativity on satisfaction: negative behaviors proved to be more important for overall satisfaction when partners show less affection then when they show more affection. We also tested the differences in patterns of interaction between spouses as a function of gender, age, length of marriage and family structure. Effects of these differences on relationship satisfaction are discussed.